Transcriptomic and metabolomic insights into the antimicrobial effect of Leuconostoc mesenteroides or lactic acid on pathogenic Gallibacterium anatis - Hua Zhang; HePing HuangFu; GuangYong Qin; GuoFang Wu; Lei Wang; ZhongFang Tan (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Gallibacterium anatis (G. anatis) is an opportunistic poultry pathogen that poses a threat to human health via the food chain and can also lead to great economic losses in poultry industries. Our previous studies have demonstrated that the lactic acid-producing bacteria Leuconostoc mesenteroides QZ1178 can effectively inhibit the growth of G. anatis by acid production, but the mechanism remains unclear. The aim of the current research was to further investigate the molecular mechanism underlying this acid-induced antimicrobial effect. The TEM results showed that the cell membrane of G. anatis (GAC026) was damaged and that cells were lysed in the presence of cell-free supernatants from Leuconostoc mesenteroides (CFS) or lactic acid. Lactic acid showed a greater antimicrobial effect than CFS. In this study, the changes in the transcriptome and metabolic profile of G. anatis under acid stress at different stages were studied. Using culture medium supplemented with CFS (pH 3.6) or lactic acid (pH 3.6) at a 1:1 ratio, 677 differentially transcribed genes and 374 metabolites were detected in G. anatis. The interaction network of all identified differentially expressed genes and metabolites was constructed to outline the regulatory genes and dominant pathways in response to acid stress. The results of real-time reverse transcription quantitative PCR (RT‒qPCR) further confirmed the results of the transcriptomic analyses. Typically, succinate, citrate, L-malic acid, and oxaloacetate were reduced by acid stress in G. anatis, which suggested that lactic acid greatly disturbed energy metabolism. Overall, this work provides a comprehensive understanding of the stress response and cell death of G. anatis caused by lactic acid. Graphical Abstract